Quantitative Structure-Properties Relationship Studies on Physicochemical Properties of Organic Molecules Using CODESSA - Zhang, Hui; Li, Jun; Kyung Kim, Chan (Asian Journal of Chemistry, 2013)
Six physicochemical properties of organic molecules, normal boiling points, heats of vaporization, heats of sublimation, heats of fusion, liquid density and solid density, were predicted by quantitative structure-properties relationship (QSPR) approach. The molecules in each set were optimized using semi-empirical AM1 and PM3 hamiltonians and verified as minima from frequency calculations using the same levels of theory. CODESSA package was then used to calculate molecular descriptors and to perform linear regressions to find out the dual-parameter equations. The results of best correlations were similar to those published earlier. The method applied in this work can be extended to predict other physicochemical properties with confidence.